A funkcionális lisztek ismertségének vizsgálata megkérdezések tükrében - Panyor, Ágota (Jelenkori Társadalmi és Gazdasági Folyamatok, 2007)
The unhealthy nutrition, wrong style of living and stress can have a major contribution to the development of certain diseases. The appearance of foodstuffs playing important role in health promotion may have a positive impact on blocking or reversing the above mentioned process. That's the reason why I chose functional food-products and the consumption habits of the functional flour. Under my examinations 1 investigated the notoriety, reputation and consumption frequency of functional flour. Besides I tried to explore the reasons resulting in the non-consumption of these food-products.